Profile of exogenous drug intoxications in the Northeast region of Brazil (Research, Society and Development, 2022)
Objective: to analyze the epidemiological profile of exogenous intoxication caused by medication in the Northeast region of Brazil from 2012 to 2021. Methodology: This is an epidemiological, retrospective, descriptive study, addressing the quantitative research method, with data collection carried out between September and October 2022, through access to the Notifiable Diseases Information System (SINAN), which is a database belonging to the Department of Informatics of the Unified Health System (DATASUS). Results: 277,306 cases of exogenous intoxication were reported in the Northeast region, of which 111,748 (40.30%) were caused by drugs, revealing the year 2012 (4.89%) with the lowest year of notification and 2019 (17 .26%) the highest. With a greater predominance of females (69.48%), of mixed race (59.88%), with the age group of 20-39 years (38.55%), followed by pediatric individuals aged